The "Cherubim song" genre in ukrainian musical culture - Shapovalova, Liudmyla; Govorukhina, Nataliya; Zinchenko, Viktoriia; Varavkina-Tarasova, Nadiia; Derkach, Larysa (MAGNANIMITAS Assn., 2023)
The genre of the Cherubim song is considered in the art criticism and sociocultural (spiritual) planes. The study of variations of the Cherubic Hymn proposed by various authors - from the liturgy of John Chrysostom to contemporary compositions by Lesya Dichko – was carried out. In general, the study was conducted in the landscape of Ukrainian sacred choral music and Christian spirituality emboedied in church music.
Keywords: Музична культура українська, перекладені пісні, композитори українські, музика хоральна українська, музика християнська